PEMBERDAYAAN MASYARAKAT PEDESAAN: INTERVENSI BERBASIS KOMUNITAS UNTUK MENINGKATKAN LITERASI KESEHATAN JIWA (Jurnal AbdiMas Nusa Mandiri, 2026)
Mental health has become an important aspect in the strategic efforts to develop public health in Indonesia, particularly in rural areas. The physical, socio-economic, cultural, and societal structural conditions contribute to the emergence of various psychological issues within the community. The main mental health problems may stem from a lack of public understanding about mental health issues, the presence of negative stigma surrounding mental disorders, and the unequal distribution of mental health services. This indicates the need for community knowledge-based programs to enhance public participation in mental health initiatives. Therefore, this activity aimed to improve the knowledge of the residents of Cijambe Village to foster a better understanding of mental health, as well as the prevention and management of mental health problems. The community service activity was conducted in the form of health education using a lecture method supported by PowerPoint media. The health education activity was attended by 37 residents of Cijambe Village, Paseh Sub-district, Sumedang Regency, West Java. The results of the knowledge level assessment showed an increase in participants’ average knowledge scores before and after the health education, from the "less" category (43%) to the "sufficient" category (57%), based on Arikunto’s knowledge level measurement scale. This health education activity achieved an outcome in the form of increased community knowledge regarding mental health as a result of the education provided. Thus, increasing public knowledge through mental health education can strengthen community participation in the prevention and handling of mental health issues at the community level.